A Web-Based Violence Reporting Application for Women and Children: A Case Study of the SP Sambe Women’s School Community in Tiley Pantai Village Using the Waterfall Development Model - Imam Hizbullah; Muhammad Natsir Rahman; Hafid Syaifudin (PROtek : Jurnal Ilmiah Teknik Elektro, 2026)
Violence against women and children constitutes a serious and escalating social problem; however, reporting rates remain critically low due to the absence of safe, accessible, and confidential reporting mechanisms. This study aimed to develop a web-based violence reporting application for the SP Sambe Women’s School (Sekolah Perempuan/SP) community in Tiley Pantai Village, Morotai Island Regency. The application was developed using the waterfall software development model, which encompasses four sequential phases: requirements analysis, system design, development, and testing. Data were collected through structured observation and in-depth interviews with prospective end-users. The results indicate that the application’s core features include anonymous incident reporting, report tracking via unique system-generated codes, role-specific dashboards for administrators and officers, and a case follow-up management module. Black-box testing confirmed that all implemented features functioned in accordance with the specified requirements. The application is expected to facilitate rapid, secure, and confidential reporting for community members, while simultaneously improving the efficiency of case management and administrative oversight for the SP Sambe community. This study affirms that the strategic utilisation of information technology can meaningfully contribute to the resolution of complex social problems, particularly those pertaining to violence against women and children.